The Incomplete Mirroring of the American Dream by Gatsby’s Character in The Great Gatsby - Anjani, Ni Made Dina Ayu; Asty Senja Pratiwi, Putu Ayu; Sumaryana Putra, I Komang (Humanis, 2025)
This article entitled The Incomplete Mirroring of the American Dream by Gatsby’s Character in The Great Gatsby, aims to explore the incomplete mirroring of the American Dream by Gatsby’s character in The Great Gatsby movie adaptation in 2013, focusing on Gatsby’s character development and the desires that drive him to pursue the American Dream. This study applied psychoanalysis theory developed by Lacan to find out how Gatsby’s character development through Lacan’s three orders and objet petit a. It explores how his identity is shaped by both his fantasies (Imaginary) and societal expectations (Symbolic). Lacan's theory shows the clash between Gatsby's dreams and the harsh truths he faces. Daisy's role as the unattainable desire, or objet petit a, that disrupts Gatsby's dream. Using a qualitative research method, the primary data was taken from the 2013 movie The Great Gatsby. The result of the study shows that his formation from James Gatz, seeks wealth to escape his poor background (the real), then he creates idealized version of himself as Jay Gatsby (the imaginary) to win Daisy’s love (objet petit a). The symbols from the society, like the green light and large parties, keep him trapped in emptiness. His story warns that becoming obsessed with illusion can lead to loneliness when those illusions fade away.